2003
DOI: 10.1016/s0735-1097(03)00299-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intermittent claudication with beraprost sodium, an orally active prostaglandin I2analogue

Abstract: Despite previous investigations suggesting efficacy, these results indicate that beraprost is not an effective treatment to improve symptoms of intermittent claudication in patients with PAD. The potential benefit of beraprost on critical cardiovascular events would require confirmation in a larger prospective investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 19 publications
1
42
1
Order By: Relevance
“…Mohler et al reported another double-blinded, randomized, controlled trial using beraprost sodium, an orally active prostaglandin I 2 analogue for the treatment of intermittent claudication. 19) Beraprost did not improve symptoms of intermittent claudication in patients with peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Mohler et al reported another double-blinded, randomized, controlled trial using beraprost sodium, an orally active prostaglandin I 2 analogue for the treatment of intermittent claudication. 19) Beraprost did not improve symptoms of intermittent claudication in patients with peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, the results of two randomized trials comparing oral prostacyclin derivatives with placebo in peripheral arterial disease were less impressive. 6,19) The first one was The European Thromboangiitis obliterans (Buerger's disease) study. 6) In this double blind, randomized, placebo-controlled trial, no significant difference was found between groups for the total healing of lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One placebo-controlled 6-month trial found that oral beraprost improved pain-free and maximal walking distance (388). Two randomized, controlled trials of 6 months' duration of patients with intermittent claudication failed to demonstrate any effect on walking distance with either oral beraprost or iloprost, although cardiovascular ischemic events were reduced in the beraprost-treated group (389). Frequent adverse effects included headache, flushing, and gastrointestinal distress.…”
Section: Medical and Pharmacologicalmentioning
confidence: 99%
“…The results obtained in previous studies also suggested that other agents with vasodilatory activities such as synthetic prostacyclin analogues may have beneficial effects not only on local symptoms but also on overall cardiovascular events. 20,23 However, these were small studies not primarily designed to evaluate vascular events. Buflomedil is an ␣-blocker with vasoactive and hemorheologic properties, 7-10,16,17 but whether it would be effective in patients already treated with other vasodilator (eg, angioten-sin-converting enzyme inhibitors or calcium blockers) or rheological (eg, cilastazol) drugs is currently unknown.…”
Section: Limb Study Group Buflomedil and Peripheral Vascular Diseasementioning
confidence: 99%